About the Role of Porosity and Surface Chemistry of Phosphorus-Containing Activated Carbons in the Removal of Micropollutants - Ruiz-Rosas, Ramiro; García-Mateos, Francisco J.; Gutiérrez, María del Carmen; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2019)
The preparation of phosphorus-containing activated carbons and the effect of their surface chemistry and porosity on the performance as adsorbents of paracetamol are herein reported. A parent activated carbon is prepared by chemical activation of olive stones with phosphoric acid at 500 ºC and impregnation weight ratio of 3:1. This carbon is thermal treated in inert atmosphere at 900 ºC, producing porosity shrinkage, loss of 20% of surface area and less oxidized phosphorus groups. In addition, our knowledge about the redox behavior of P-containing groups has allowed the controlled gasification of the parent activated carbon in diluted air atmosphere, developing wide micropores and mesopores, increasing 40% the specific surface area and producing more oxidized phosphorus groups. Adsorption of a model micropollutant, paracetamol, has been conducted over these activated carbons using diluted aqueous solutions (<10 mg L-1). Batch and small-scale column experiments confirmed that the presence of narrow microporosity and surface chemistry compatible with paracetamol improves the adsorption capacity, at the point of overcoming the potential effect of additional microporosity development. Moreover, the presence of a well-developed micro- and mesoporisity combined with a low surface acidity (that increases the affinity of the activated carbon surface and paracetamol) enhances the mass transfer rate of the adsorbent, improving the small-scale column performance parameters. These results also confirm that controlled gasification at high temperatures of P-containing activated carbons is an useful method for improving their behavior in micropollutant abatement.